1974
DOI: 10.1085/jgp.64.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Chronotropic Agents in Cardiac Purkinje Fibers

Abstract: Hauswirth et al. (1968) proposed that epinephrine acts on i, by adding its own positive charge to the external membrane surface near the iK, channel. This hypothesis was tested by using noncationic compounds, theophylline and R07-2956, which mimicked epinephrine's effects on pacemaker activity and on ix,. In maximally effective doses, theophylline or R07-2956 occluded the effect of epinephrine, indicating a shared final common mechanism. Since theophylline and R07-2956 are noncationic at pH 7.4, the common mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1977
1977
1997
1997

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…,l-Agonists speed the activation of if by shifting its activation curve to more positive potentials; this has been shown to correlate with an increase in the intracellular cyclic AMP levels (Tsien, 1974b). Our results show that the protein kinase inhibitors H-7 and H-8, eliminate the effect of isoprenaline on both diastolic depolarization and on pacemaker current if.…”
Section: Fl-agonists Regulate If Via Phosphorylationmentioning
confidence: 51%
See 1 more Smart Citation
“…,l-Agonists speed the activation of if by shifting its activation curve to more positive potentials; this has been shown to correlate with an increase in the intracellular cyclic AMP levels (Tsien, 1974b). Our results show that the protein kinase inhibitors H-7 and H-8, eliminate the effect of isoprenaline on both diastolic depolarization and on pacemaker current if.…”
Section: Fl-agonists Regulate If Via Phosphorylationmentioning
confidence: 51%
“…This mechanism of ion channel regulation has been demonstrated for Ca2+ channels (see reviews, Tsien, 1977; Reuter, 1979Reuter, , 1983Tsien, Bean, Hess & Nowycky, 1983;Sperelakis, 1985;Trautwein & Hescheler, 1990) and delayed rectifier potassium channels (Tsien, Giles & Greengard, 1972;Walsh, Begenisich & Kass, 1988;Duchatelle-Gourdon, Hartzell & Lagrutta, 1989). For if, it has been known that the voltage shift of the activation curve induced by isoprenaline is accompanied by an elevation of intracellular cyclic AMP levels (Tsien, 1974b). However, whether the increase in cyclic AMP leads to a phosphorylation which underlies the increase in if remains uncertain.…”
Section: Introductionmentioning
confidence: 86%
“…This view was supported by a further series ofexperiments using theophylline. This phosphodiesterase inhibitor was found by Tsien (1974b) to occlude the shift produced by adrenaline, when both were in maximally effective doses 1 mm and 5 x 10-6 M respectively. He found that in submaximal does their effects were synergistic.…”
Section: Pace-maker Current In Sheep Atriummentioning
confidence: 92%
“…It could thus be argued that our control solutions, containing barium and Mg2+ would occlude such an effect, by the screening effect of divalent ions. However, Tsien (1974b) showed that the shifts in the activation curves produced by adrenaline and lanthanum ions were not exclusive, but additive. In order to test whether the omission of Mn2+ would change the effects of adrenaline, D-600 was used as a blocker of the slow inward channel, instead of manganese, in seven preparations.…”
Section: Pace-maker Current In Sheep Atriummentioning
confidence: 99%
“…These substances increase if by shifting the activation curve to more positive voltages without changes in maximal conductance. cAMP increases if by shifting the activation curve to more positive voltages with no change in maximal (Tsien, 1974;DiFrancesco, Ferroni, Mazzanti & Tromba, 1986) or single-channel conductance (DiFrancesco & Mangoni, 1994). In nodal cells, the shift is due to a direct interaction of intracellular cAMP with f-channels, according to a phosphorylation-independent mechanism (DiFrancesco & Tortora, 1991).…”
Section: Measurement Of the Conductance-voltage (Gf (V)) Relation By mentioning
confidence: 99%